2005
DOI: 10.1063/1.2103402
|View full text |Cite
|
Sign up to set email alerts
|

Deducing nanopore structure and growth mechanisms in porogen-templated silsesquioxane thin films

Abstract: Adjusting the functional group of a porogen is found to have a tremendous effect on the pore structre of porous low dielectric constant films with silsesquioxane as the matrix precursor. The pore size and interconnection length measured by positronium annihilation lifetime spectroscopy can be used to deduce the pore shape and its evolution with porosity from templates of isolated porogen molecules through film percolation. Inert, self-linkable, and amphiphilic porogens are demonstrated to randomly aggregate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The explosive growth of the pores using CA [6] suspected from our earlier results [16,17] is now clearly demonstrated in Figs. 2-4.…”
Section: Characterization Of Fully Cured Ssq/ca[6] Films Of Varying Pmentioning
confidence: 52%
See 2 more Smart Citations
“…The explosive growth of the pores using CA [6] suspected from our earlier results [16,17] is now clearly demonstrated in Figs. 2-4.…”
Section: Characterization Of Fully Cured Ssq/ca[6] Films Of Varying Pmentioning
confidence: 52%
“…In this application the porogen molecules integrated into the matrix material would ideally be isolated from each other, thus providing a template for isolated nanopores the size of only the porogen molecule. However, with increasing porogen concentration, the porogen-porogen interaction may dominate compared to that of the porogen-matrix thus leading to greater aggregation of the porogen domains and the resulting pores are likely to be highly interconnected [16]. Thus, lowering k by increasing porosity reaches a limit when the pore structure becomes unacceptably susceptible to integration damage.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the fracture toughness of the TESNB films was superior to the TMSNB films as well as the base MSQ material. Peng et al [ 66 ] found that porogen functional groups strongly affect the final pore structure in their study of silsesquioxane-based films. As was the case for PECVD films, it is possible to create labile phases without a separate porogen precursor.…”
Section: Dielectric Deposition Processesmentioning
confidence: 99%
“…By studying the evolution of both the pore size and the pore interconnection length PALS can begin to deduce the shape of the pores and delineate the relative strength of the porogen-porogen interaction with respect to the porgen-matrix interaction. A recent study of the growth of pores in the prepercolation regime was made by using PALS on films with several cyclodextrin (CD) and calix-arene www.pss-c.com (CA) porogens with various functional groups in a modified MSQ host matrix [15]. Results for the pore diameter and L int for films prepared with tCD (CD with methoxyl functional groups) sCD (CD with trimethoxyl-silyl functional groups) and CA are shown in Fig.…”
mentioning
confidence: 99%